The relevance of SPS in the ACP-EU economic partnership agreements: What a development-friendly recognition of SPS measures within the EPA negotiations might look like - Christine Chemnitz; Doris Günther (Humboldt-Universität zu Berlin, Wirtschafts- und Sozialwissenschaften an der Landwirtschaftlich-Gärtnerischen Fakultät, 2007)
The Africa Caribbean and Pacific (ACP) countries have benefited from unilateral preferential access to EU markets under various trade agreements. However, since agricultural trade is increasingly determined by food safety and quality standards, one of the main concerns of ACP countries is their inability to benefit from their preferential status due to their lack of compliance with EU food quality requirements. Recently, this dilemma has become of particular interest because the unilateral preferential access provided under the Cotonou Agreement no longer conforms with World Trade Organization (WTO) law, instead reciprocal trade agreements, the Economic Partnership Agreements (EPAs), should replace the former ones in 2008. ACP countries' ability to access EU markets and thereby gain from the new trade agreements largely depends on the progress they have made in adjusting their food safety systems to international standards. It is therefore essential to incorporate legally binding provisions into the EPAs that address the particular difficulties of ACP countries regarding SPS issues. This paper aims to develop a checklist for the development-friendly recognition of SPS measures in the EPA negotiations.
Keywords: F13; F19; 330; EPA; SPS; ACP; Food Safety